The effectiveness of negative-pressure wound therapy in the treatment of Fournier’s gangrene – a literature review - Maj, Filip Jacek; Sornat, Karol Bartłomiej; Estreicher, Agata; Klasa, Anna Maria; Sobaś, Aleksandra Ewa; Biedka, Kamil; Ziobro, Oliwia; Błaszczyk, Katarzyna; Pokora, Barbara; Bulski, Jakub (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2025)
The purpose of our study was to compare vacuum-assisted closure (VAC) and conventional dressings in the wound therapy of Fournier’s gangrene. On 3 November 2024 the MEDLINE database was searched. The following search query was used: “Fournier gangrene AND negative-pressure wound therapy” with one filter “free full text”. The initial search returned 38 results. After screening of abstracts, 28 results were chosen for full text analysis, 6 of which met inclusion criteria and were included in the study. The average hospitalization time for the group with conventional dressings was 22.8 days, while for the group with VAC therapy was 24.8 days. In contrast, the average time from initial surgical debridement to wound closure for conventional dressings was 49.5 days, compared to 40 days for VAC therapy. Our study showed that the average hospitalization time was shorter for patients treated with conventional dressings than for those treated with VAC therapy. In contrast, the average time from initial surgical debridement to wound closure was shorter for the VAC method than for conventional dressings.